SEASONAL CHANGES OF GONADOSOMATIC INDEX OBSERVED IN THE FRESHWATER FISH CHANNA PUNCTATUS - SUNITA KAPIL; K. M. KULKARNI; S. S. GIJARE; V. T. TANTARPALE (The Bioscan, 2011)
In the present study the values of gonadosomatic index of freshwater fish Channa punctatus collected from Wadali lake near Amravati region of Maharashtra during 2006- 07. The minimum gonadosomatic index for females (0.285) observed in winter season. The maximum gonadosomatic index values of ovaries were observed in rainy season (0.775) and intermediate values of gonadosomatic index were in Summer (0.472). The gonadosomatic index for males were (0.62 in summer, (0.74) in rainy and (0.42) in winter.